Real-Time Muscle Activity and Joint Range of Motion Monitor to Improve Shoulder Pain Rehabilitation in Wheelchair Basketball Players: A Non-Randomized Clinical Study - Giacomo Farì; Marisa Megna; Pietro Fiore; Maurizio Ranieri; Riccardo Marvulli; Valerio Bonavolontà; Francesco Paolo Bianchi; Filomena Puntillo; Giustino Varrassi; Victor Machado Reis (Clinics and Practice, 2022)
Wheelchair basketball (WB) involves sports gestures that expose the shoulder to high biomechanical stress and frequently lead to shoulder pain (SP). Due to their physical peculiarities and sporting performance, these athletes require specific rehabilitation programs that are as fast, personalized and effective as possible. However, there are few studies specifically dedicated to these purposes. Surface electromyography (sEMG) seems a promising tool for better customization and achieving more targeted rehabilitation results. The aim of this study was to evaluate the usefulness of sEMG to monitor SP rehabilitation outcomes in WB players. Thirty-three athletes were enrolled in this non-randomized clinical study and divided into two groups. Both groups underwent a shoulder rehabilitation protocol, but only the experimental group was monitored in real time with sEMG on the shoulders. At enrollment (T0), at the end of 4 weeks of the rehabilitation program (T1), and 8 weeks after T1 (T2), the following outcome measures were collected: Wheelchair User’s Shoulder Pain Index (WUSPI), 20 m straight line test, shoulder abduction range of motion (ROM). There was a statistically significant difference for WUSPI and ROM scores in the comparison between groups (p < 0.001), and for all outcomes in the comparison between times and in the interaction between time and group (p < 0.001). Therefore, the experimental group showed a better improvement at all detection times compared to the control group. sEMG seems a useful tool for improving the monitoring of SP rehabilitation outcomes in WB players. This monitoring speeds up and improves the rehabilitative results, limiting the risk of sport abandonment and increasing the possibility for people with disabilities to quickly return to practice physical activity.